Curcumin-Loaded Lipid Nanoparticles: A Promising Antimicrobial Strategy Against Enterococcus faecalis in Endodontic Infections - Sónia Ferreira; Liliana Grenho; Maria Helena Fernandes; Sofia A. Costa Lima (Pharmaceutics)
Background/Objectives: This study aims to evaluate the efficacy of curcumin (CUR), a natural polyphenol with potent antimicrobial and anti-inflammatory properties, when formulated as solid lipid nanoparticles (CUR-loaded SLN) against Enterococcus faecalis. Methods: Solid lipid nanoparticles (SLNs) were prepared as a carrier for CUR, which significantly improved its solubility. SLNs made with cetyl palmitate and Tween 80 were obtained via the hot ultrasonication method. The physicochemical properties of CUR-loaded SLNs were evaluated, including their size, stability, and release profile. Antimicrobial testing was conducted against both sessile and planktonic E. faecalis populations. Cytotoxicity was assessed on human gingival fibroblasts. Results: The CUR-loaded SLNs exhibited about 200 nm and a −25 mV surface potential, and the encapsulation of CUR did not affect the physicochemical properties of SLNs. CURs were released from SLNs in a controlled and sustained manner over 100 h. The nanoparticles remained stable for at least two months when stored at 4 °C or 25 °C, making them suitable for clinical use. Antioxidant activity was confirmed through DPPH and ABTS assays. Free CUR significantly reduced the planktonic E. faecalis CFU counts by approximately 65% after 24 h of exposure. However, this inhibitory effect diminished with longer exposure times (48 and 72 h). Antimicrobial activity studies of CUR-loaded SLNs showed dose- and time-dependent effects, in the 2.5–10 µg/mL range, against both sessile and planktonic E. faecalis populations, over 24 to 72 h. The CUR-loaded SLNs showed good cytocompatibility with human fibroblasts up to 2.5 μg/mL, suggesting low toxicity. Conclusions: CUR-loaded SLNs demonstrate significant antimicrobial activity against E. faecalis, along with good cytocompatibility, indicating their potential as an effective adjunct therapy in endodontic treatments.